Anglican Bishop's residence - Khan, Farouk (Print Master Limited, Trinidad, 2010)
Description on the back of the postcard:"Also call Hayes Court. This Typical grand house, styled with a pleasant mixture of French and English. It was built in 1910 and has always been the residence of the Bishops of the Anglican Diosces[sic]."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bishops--Dwellings--Trinidad and Tobago; Anglicans--Trinidad and Tobago; Historic buildings--Trinidad and Tobago